Leucoagaricus viridariorum (Agaricaceae, Agaricales), a new species from Spain - Munoz, Guillermo; Caballero, Agustin; Salom, Joan Carles; Ercole, Enrico; Vizzini, Alfredo (Phytotaxa, 2015)
Leucoagaricus viridariorum is proposed as a new species based on material collected in different areas of Spain. This taxon is characterised macroscopically by its small, whitish basidiomes, minutely squamulose-fibrillose pileus, evanescent ascendant annulus and growth in man-made environments. Microscopically, its subglobose to broadly ellipsoid spores, the clavate cheilocystidia and the trichodermic pileipellis are diagnostic. Based on molecular data of the internal transcribed spacer of nuclear ribosomal DNA (nrITS) this species belongs to the Leucoagaricus/Leucocoprinus clade of the Agaricaceae where it is sister to Leucoagaricus amanitoides.